2018
DOI: 10.1016/j.drugalcdep.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Loaded: Gun involvement among opioid users

Abstract: Opioid users, both men and women, lead gun-involved lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
0
3
1
Order By: Relevance
“…Within this sample, we found no differences in firearm access according to particular admission diagnosis. This is in contrast to a past study of patients undergoing medication-assisted withdrawal which showed higher rates of firearm involvement for those undergoing opioid detoxification compared to those undergoing alcohol detoxification (33.9% vs. 31.4%, respectively) ( Stein et al., 2018 ). The reasons for this remain unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Within this sample, we found no differences in firearm access according to particular admission diagnosis. This is in contrast to a past study of patients undergoing medication-assisted withdrawal which showed higher rates of firearm involvement for those undergoing opioid detoxification compared to those undergoing alcohol detoxification (33.9% vs. 31.4%, respectively) ( Stein et al., 2018 ). The reasons for this remain unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…This study provides a rare look into firearm access rates among patients with substance use disorders, particularly within the inpatient detoxification setting. While a previous study asked patients undergoing detoxification about gun ownership or access within the last year ( Stein et al., 2018 ), we believe ours is the first to assess patients undergoing detoxification for current access to a firearm. We found that employing standard suicidal screening procedures in detoxification settings can yield high rates of completed clinical documentation for firearm access, providing more accurate figures for this important suicide and violence risk factor in this high-risk group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found striking levels of gun involvement in a sample of opioid abusers enrolled in a detoxification program. Compared with alcohol abusers, the opioid abusers were significantly more likely to have been threatened with a gun (45 percent v. 26 percent), carried a gun for protection (31 percent v. 4 percent), and shot at another person (14 percent v. 2 percent) (Stein et al 2018).…”
Section: Introductionmentioning
confidence: 99%